Nature Conservation in Brazil in the 20th Century - Franco, José Luiz de Andrade; Drummond, José Augusto (Historia Ambiental Latinoamericana y Caribeña (HALAC) revista de la Solcha, 2024)
The text explores actors and institutions involved in the conservation of nature in Brazil during the 20th century. It seeks to understand their ideas, themes and proposals while also focusing on their activism. It deals with convergences and divergences between activists and organizations considering the political contexts in which they operated. We conclude that the continuity among actors was difficult but highly important and that it led to the development of integrated public policies that conserve biodiversity and promote the controlled and equitable use of natural resources. We also identified the relevance of ecocentric  environmental ethics, focused on the notion that all species have an intrinsic value.